Selective Electroless Silver Deposition on Graphene Edges. Issue 6 (1st January 2015) - Durhuus, D.; Larsen, M. V.; Andryieuski, A.; Malureanu, R.; Pizzocchero, F.; Bøggild, P.; Lavrinenko, A. V.
Abstract : We demonstrate a method of electroless selective silver deposition on graphene edges or between graphene islands without covering the surface of graphene. Modifications of the deposition recipe allow for decoration of graphene edges with silver nanoparticles or filling holes in damaged graphene on silica substrate and thus potentially restoring electric connectivity with minimal influence on the overall graphene electrical and optical properties. The presented technique could find applications in graphene based transparent conductors as well as selective edge functionalization and can be extended to other metals than silver.